Lymphatic mapping Of Oropharyngeal Cancer (LOOC): protocol for a phase II surgical imaging trial to evaluate contralateral drainage and occult metastasis in oropharyngeal cancer - David Walker; Gareth Ambler; Chris Brew-Graves; Jason Fleming; Vinidh Paleri; Richard Shaw; Mark McGurk; Enyi Ofo; Clare Schilling; Karl Payne; Simon Wan; Alex Weller; et al. (BMJ Open)
Introduction Treatment of the node negative contralateral neck in oropharyngeal cancer (OPC) remains debated, with no clear consensus. Prophylactic contralateral neck treatment (either surgically or via irradiation) is generally recommended when the estimated risk of occult nodal metastasis is >20%. Unfortunately, patients undergoing bilateral neck treatment often require long-term supportive care for swallowing dysfunction. Reducing the impact of treatment on long-term quality of life is key in patients with OPC who have a good prognosis and tend to be young and fit at presentation. Lymphatic mapping and the use of free-hand single photon emission CT (fhSPECT) combined with sentinel lymph node biopsy is a novel approach to address this clinical need. The Lymphatic mapping Of Oropharyngeal Cancer trial aims to (a) validate a lymphatic mapping protocol in OPC using new technology (fhSPECT) with radiotracers and (b) establish lymphatic drainage patterns and the occult metastatic rate in the contralateral neck in OPC.Methods and analysis The design is a prospective multicentre cohort trial to understand the lymphatic drainage pattern in 150 patients with OPC and unilateral neck metastases. The trial has two phases: (1) imaging phase (n=75)—aim: develop an imaging protocol to establish the lymphatic drainage pattern in a population of patients with proven unilateral neck metastasis from OPC. The intervention will involve peritumoural injection of radiotracer followed by fhSPECT scan under general anaesthesia (GA) (at time of examination under anaesthetic). A SPECT/CT scan (gold standard for lymphatic mapping) will be carried out subsequently as a comparator. The primary outcome is the rate of contralateral drainage. Secondary outcome is the accuracy of fhSPECT versus SPECT/CT. The number of contralateral nodes on SPECT/CT will be used as the denominator in calculating the sensitivity of fhSPECT in independently verified images. fhSPECT should achieve sensitivity >94%. A minimum number of 20/75 patients will be required to demonstrate contralateral drainage to proceed to the surgical stage. An imaging substudy (n=20) aims to develop a secondary imaging protocol in the event of <94% sensitivity of intraoperative fhSPECT. To investigate the sensitivity of outpatient imaging (single injection of radiotracer and SPECT/CT) compared with gold standard (SPECT/CT from initial imaging phase) and the acceptability of outpatient injection compared with under GA. Twenty patients from the imaging phase with easily accessible tumours will be invited to undergo a second imaging; (2) Surgical phase (n=75)—aim: demonstrate the utility of surgically staging the contralateral neck using sentinel node biopsy (SNB). The primary outcome of this surgical phase is the occult metastatic rate of contralateral nodes (positive SNB). The contralateral drainage rate will be identified during the imaging phase, with an expected SNB positive rate of excised nodes ranging from 25% to 40%.Ethics and dissemination The outcome of this trial will provide a validated protocol and evidence to inform the design of future research in which management of the contralateral neck is based on surgical staging. Ethical approval was granted by the Yorkshire & The Humber-South Yorkshire Research Ethics Committee (REC ref: 20/YH/0111). Results from the trial will be presented to the scientific community at appropriate meetings and international journals. Patients and the public will be informed via patient groups, cancer charities and social media/press releases.Trial registration number NCT04498221.